(untitled) (Faridpur Medical College Journal, 2020)
Kikuchi-Fujimoto disease is a rare benign, condition of necrotizing histiocytic lymphadenitis. Presenting complaints of neck masses in association with non-specific systemic signs and symptoms prompt investigation towards the more common diagnoses. However, rarer conditions must still be considered especially when a patient’s condition fails to abate. Herein I discuss a case of female patient who presented with a neck mass that was not attributable to the more common causes. A 28 year old lady presented with feverish feeling, weight loss and tender cervical lymph nodes. Initially tuberculous lymphadenitis was suspected but Kikuchi-Fujimoto disease was diagnosed after cervical lymph node biopsy. Symptomatic treatment was provided and an eventful full recovery was made. Faridpur Med. Coll. J. Jan 2019;14(1): 50-53